An investigation of Sharīʿah penny stocks’ performance and its determinants: evidence from Bursa Malaysia - Che Ismail, Che Muhamad Hafiz; Abideen, Adewale Abideen; Haron, Razali (IIUM Institute of Islamic Banking and Finance, 2019)
Since the introduction of Sharīʿah Status Company in Bursa Malaysia in 1997, the demand for Sharīʿah-compliant investment has increased. However, the limitations in Sharīʿah-compliant investment create worries and doubtfulness among the investors whether the Sharīʿah-compliant stocks performance can outperform the Non-Sharīʿah-compliant stocks and most importantly, maximizing the profit. Hence, this study is conducted using 40 Sharīʿah and 40 non-Sharīʿah penny stocks as the samples. Then, technical analysis is applied to determine the market timing. Based on the technical analysis on Kuala Lumpur Composite Index (KLCI), the period of study is chosen from April 2009 to July 2017. This study investigates the significant differences between risk and return. By using independent sample T test for parametric data and Mann Whitney U test for non-parametric data, the result shows that there is no significant difference in terms of risk and return between Sharīʿah penny stock portfolio and Non-Sharīʿah penny stock portfolio. Then, risk adjusted return measurements; Sharpe Ratio, Treynor Ratio and Jensen’s Alpha are employed to calculate risk adjusted return. From the result, Sharīʿah penny stocks portfolio is better in terms of risk adjusted return compared to the conventional portfolio.